Hippocampal Slices: On‐Chip Ultrasound Modulation of Pyramidal Neuronal Activity in Hippocampal Slices (Adv. Biosys. 8/2018). Issue 8 (14th August 2018) - Lin, Zhengrong; Zhou, Wei; Huang, Xiaowei; Wang, Kaiyue; Tang, Jie; Niu, Lili; Meng, Long; Zheng, Hairong
Abstract : In article number1800041, Lili Niu, Long Meng, Hairong Zheng, and co‐workers develop an ultrasound neuro‐modulation chip to modulate neural activity. Ultrasound stimulation activates neurons and enhances neuronal excitability via elevation of sodium currents. This chip provides a simple and powerful tool for understanding the mechanism of ultrasound neuromodulation.